Teacher Strategies in Independent Curriculum Management to Improving 21st-Century Competencies at SMPIT Madani Tanjung Redeb-Berau - Rini Rini; Bambang Sudarsono; Suyatno Suyatno (Bulletin of Pedagogical Research, 2025)
In today's modern era and technological advancements, innovation is needed to meet the needs of human life, especially in the field of education. Relevant curriculum updates are a step that can be taken to achieve this. The revised curriculum is expected to improve the quality of education. The purpose of this article is to explain how SMPIT Madani implements the Independent Curriculum to achieve optimal results. This study uses a descriptive qualitative method with data collection techniques such as interviews, observations, and document reviews. The results of this study in its implementation strategy. At SMPIT Madani, the implementation of this curriculum emphasizes a student-centered learning approach, where the needs and potential of students are the main focus. This curriculum also provides flexibility for teachers to develop creative and innovative learning according to student characteristics. Thus, students have the opportunity to develop 21st-century competencies, namely the 4Cs: critical thinking, communication, collaboration, and creativity. Learning in the Independent Curriculum also emphasizes a project-based approach that aims to shape the character of Pancasila Students, as well as strengthening intracurricular activities as part of the learning process. Furthermore, teachers are required to select learning strategies, models, and methods that are appropriate to their students' needs and capable of integrating technology. The goal is to equip students with relevant and applicable skills for real-life use in the modern era.